Reform strategy for primary education in the Organization of Eastern Caribbean States. - Sutton, Leroy A. (1990)
Outlines a possible programme to address the shortcomings of primary education. Taking note of the limited resources, suggests the need for reform in teacher training, curriculum change, transition from primary to secondary school, record keeping, development of pastoral care programmes, and mainstreaming of mildly handicapped pupils.